Predictors of Capacity-Building Needs Among Nongovernmental Organizations in Sub-Saharan Africa. Issue 2 (3rd April 2018) - Despard, Mathieu R.; Ansong, David; Nafziger-Mayegun, Rhoda Nanre; Adjabeng, Bernice
ABSTRACT: Nongovernmental organizations (NGOs) play important roles in social development in the Global South. However, little evidence exists concerning NGOs' capacity-building needs. We sought to understand organizational and network factors that explain capacity-building needs. Using an online survey of 282 NGOs in Ghana, Kenya, and Nigeria, we found high levels of capacity-building need, particularly concerning resource development. Using multivariate analyses, we found greater staff size predicted less overall capacity-building need based on a 15-item index (α = .88). Examining individual capacities, receiving at least half of funding from international sources and prior capacity-building assistance were consistent predictors of lower odds of capacity-building need.